The business 2.0. B1+ intermediate, - Allison, John; Emmerson, Paul (Macmillan, 2013)
Building the next business generation
Keywords: angličtina; obchodní komunikace; English language; communication in business; jazykové učebnice, texty, příručky (B); language textbooks, texts, handbooks (B)